Surgical Options for Patellar Stabilization in the Skeletally Immature Patient. Issue 2 (June 2017) - Andrish, Jack
Abstract : The surgical management of children and youth with patellar instability can be a challenging exercise. It is possible to identify the various pathoanatomies that coexist with and predispose to patellar instability and in so doing, it is possible to address some, but not all, of these pathoanatomies as part of the surgical management. Although reconstruction of the medial patellofemoral ligament has become a mainstay of treatment, it is not without potential complications. Understanding the importance of surgical technique as it relates to the unique anatomies involved is crucial. Despite the presence of open growth plates, patellar instability in the skeletally immature patient can be effectively and safely performed.